EVALUATION OF ANTIOXIDANT, ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT IN THE LEAVES OF COMBRETUM ALBIDUM AND GAS CHROMATOGRAPHY-MASS SEPTROMETRY ANALYSIS - Chandar, Brinda; Ramasamy, Mohan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study evaluates chemical composition, antioxidant, and antibacterial activity of ethanol extract from leaves of Combretum albidum. Methods: An evaluation of antibacterial activity was carried out by the disc-diffusion method and resazurin microplate assay to determine minimum inhibitory concentration (MIC). The anti-oxidant activity was done using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method and superoxide assay. The gas chromatography-mass septrometry evaluation of C. albidum was done to analyze the phytochemical constituents that are responsible for the antimicrobial and antioxidant property. The results were compared with NIST library. Results: The disc-diffusion method showed zone of inhibition that ranged from 19.8±0.57 (Bacillus subtilis) to 9.3±0.57 (metallo-beta-lactamase producing Escherichia coli [MBLe]), and the MIC was least for B. subtilis at 0.08 mg/ml. It was found that C. albidum exhibited antibacterial activity against all the 8 Gram-negative and Gram-positive bacteria including multidrug-resistant bacteria, MBL producing bacteria, and methicilin-resistant Staphylococcus aureus. The IC value for the antioxidant activity was 156.26 µg/ml and 69.03 µg/ml for DPPH and superoxide assay, respectively. This study yielded a total of 23 bioactive compounds with potent biological activity. 50 Conclusion: The study proves the potential ability of C. albidum, suggesting its exploitation in bioactive compounds for the antimicrobial and antioxidant property. Keywords: Combretum albidum, Antioxidant activity, Antibacterial activity, Bioactive compounds.